Pengaruh Risk Tolerance Terhadap Keputusan Mahasiswa Surabaya Berinvestasi Dengan Financial Literacy Sebagai Variabel Moderasi - Masruroh, Dewi; Perwita Sari, Rida (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2021)
This study aims to test and prove the effect of risk tolerance on investment decisions and financial literacy can moderate risk tolerance on investment decisions. This research is a quantitative research with primary data. The analysis technique used is moderated regression analysis with WarpPLS 7.0 software. The study used students of the Faculty of Economics and Business, State University throughout the city of Surabaya, 2017-2018 as populations. The number of samples in this study were 100 respondents who were obtained by using purposive sampling technique. The results of the regression test show that risk tolerance affects investment decisions and financial literacy cannot moderate the relationship between risk tolerance and investment decisions.